Sediment residence times in catchments draining to the Gulf of Carpentaria, northern Australia, inferred by uranium comminution dating. (1st January 2019) - Martin, Ashley N.; Dosseto, Anthony; May, Jan-Hendrik; Jansen, John D.; Kinsley, Leslie P.J.; Chivas, Allan R.
Abstract: Uranium (U) isotopes are useful for constraining the timescales of weathering and erosion processes. The ( 234 U/ 238 U) activity ratio (parentheses denote activity ratio) of fine-grained detrital minerals is proposed to record the time elapsed since mineral grains were reduced to <63 μm in size, i.e. the comminution age . Comminution ages of river sediments theoretically represent the sum of hillslope storage and alluvial transport/storage in a catchment, i.e. the sediment residence time . Calculation of comminution ages requires knowledge of the ( 234 U/ 238 U) at comminution (i.e. in the parent material at t = 0) and the fraction of 234 U recoiled out of sediments ( direct-recoil fraction ). Furthermore, it is assumed that recoil is the only process fractionating 234 U and 238 U and there is no aeolian input. Here we infer comminution ages for river sediments from seven large catchments draining to the Gulf of Carpentaria, northern Australia. The initial ( 234 U/ 238 U) was constrained by measuring the ( 234 U/ 238 U) of visibly "unweathered" rocks collected from catchment headwaters and the direct-recoil fraction was constrained for each river sediment by surface area analyses. The ( 234 U/ 238 U) of rocks ranged from 0.795 to 1.011, suggesting that rocks undergo U isotope fractionation prior to comminution into sediments. For several river sediments, the estimated direct-recoil fraction could not account for the measured ( 234 U/ 238 U). Therefore, we adopted a modified comminution age equation to account for preferential leaching of 234 U following comminution, thereby relaxing the assumption that recoil is the only process fractionating U isotopes. Monte Carlo simulations were used to account for the uncertainty in input parameters and median comminution ages inferred without and with leaching parameters ranged from 18 to 650 ka, and 4 to 98 ka, respectively. Sensitivity analyses show that inferred comminution ages are highly dependent on the choice of the 238 U leaching rate but the ratio of the 234 U/ 238 U leaching rates is less important. For median sediment residence times inferred without leaching parameters, there are inverse correlations with mean annual rainfall (R 2 = 0.71) and vegetation cover (R 2 = 0.52), and a correlation with the rainfall seasonality index (R 2 = 0.64). However, these relationships are not observed for sediment residence times calculated using leaching parameters. This questions the validity and/or the inputs of the modified comminution age model with nuclide leaching parameters. This study addresses some of the major sources of uncertainty regarding comminution dating and provides insights for estimating sediment transport timescales in hillslope-fluvial systems.